Genomicus in 2022: comparative tools for thousands of genomes and reconstructed ancestors. Issue Volume 50:Issue D1(2022) (18th November 2021) - Nguyen, Nga Thi Thuy; Vincens, Pierre; Dufayard, Jean François; Roest Crollius, Hugues; Louis, Alexandra
Abstract: Genomicus is a database and web-server dedicated to comparative genomics in eukaryotes. Its main functionality is to graphically represent the conservation of genomic blocks between multiple genomes, locally around a specific gene of interest or genome-wide through karyotype comparisons. Since 2010 and its first release, Genomicus has synchronized with 60 Ensembl releases and seen the addition of functions that have expanded the type of analyses that users can perform. Today, five public instances of Genomicus are supporting a total number of 1029 extant genomes and 621 ancestral reconstructions from all eukaryotes kingdoms available in Ensembl and Ensembl Genomes databases complemented with four additional instances specific to taxonomic groups of interest. New visualization and query tools are described in this manuscript. Genomicus is freely available at http://www.genomicus.bio.ens.psl.eu/genomicus .